Assessment of the indication for transfusion of red blood cells according to evidence-based practice and a brief overview of education in transfusion medicine (Research, Society and Development, 2022)
Objectives:  assess whether the indications for transfusion of red blood cells in a large hospital in São Paulo follow evidence-based recommendations. Method: Quantitative and descriptive retrospective study based on obtaining information through requisition forms for Hemotherapeutic procedures. Results:  229 requisition forms were evaluated from September to October 2021. The mean age of the sample was 56.9 years ± 16.4, composed mostly of men 54.6%. Intensive care units were the places with the highest number of requests (52.4%). Symptomatic anemia was the main indication for transfusion (70.7%), followed by active bleeding (24.5%). Among the comorbidities, neoplasms (27.9%) were the most prevalent. The mean hemoglobin values were 6.84g/dL ±1.13 and the mean hematocrit values were 21.0% ± 3.42. The absolute value of hemoglobin was greater than 7.0g/dL in 40.6% of the 229 files and 10.5% of the total, with values equal to or greater than 8.0g/dL. Conclusion: the indication for red blood cell transfusions doesn’t follow the recommendations of evidence-based practice in the studied sample, being necessary to provide training to students and professionals, with the aim of improving the quality of prescribing criteria.